Differential Item Functioning of the region-based national examination equipment - Adi Setiawan; Gulzhaina Kuralbaevna Kassymova; Vianney Mbazumutima; Anggit Reviana Dewi Agustyani (REID (Research and Evaluation in Education), 2024)
This research aims to detect Differential Item Functioning (DIF) in the 2014/2015 National Examination Questions in mathematics of junior high schools and equivalent-level schools in the Yogyakarta region as a reference group and the South Kalimantan region as a focus group using the Likelihood Ratio Test (LRT) method, Area Measure Raju, and Lord. A sensitivity analysis was conducted to determine the most sensitive method. The data consisted of 5,465 National Examination papers of the students from the two regions who worked on type A questions. A sample of 1,000 exam papers for each region was established using the simple random sampling (SRS) technique, which was conducted to avoid the effect of sample size. The research results showed that by using the LRT method, the researchers found 36 items had significant DIF detection, 32 items were significant for Raju Area, and all items had significant DIF detection using Lord. Lord Method is the most sensitive method because it can detect most DIF items.